2018
DOI: 10.1108/rpj-03-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Printing with mechanically interlocked extrudates using a custom bi-extruder for fused deposition modelling

Abstract: Purpose This paper aims to target to print functionally gradient materials (FGM) devices made of immiscible polymers in multi-material fused deposition modelling (FDM) systems. The design is intended to improve adhesion of dissimilar thermoplastics without the need for chemical compatibilization so that filaments from many different sources can be used effectively. Therefore, there is a need to invent an alternative solution for printing multiple immiscible polymers in an FDM system with the desired adhesion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…The development and advancement of the modern technologies make it possible to manufacture multiple-material parts in a single manufacturing process. Khondoker et al [63] designed a static mixer inside the extrusion nozzle head of the FFF machine, which aimed to help mix the two different polymers during the deposition process. The authors revealed that intermixed specimens could increase the interface strength of FFF-made parts.…”
Section: Materials Extrusion (Me)mentioning
confidence: 99%
See 2 more Smart Citations
“…The development and advancement of the modern technologies make it possible to manufacture multiple-material parts in a single manufacturing process. Khondoker et al [63] designed a static mixer inside the extrusion nozzle head of the FFF machine, which aimed to help mix the two different polymers during the deposition process. The authors revealed that intermixed specimens could increase the interface strength of FFF-made parts.…”
Section: Materials Extrusion (Me)mentioning
confidence: 99%
“…Different materials for fabricating multi-material AM parts have been documented and studied in the literature [61,63,106]. Zhangwei et al [107] provided a review on various ceramic materials and their properties and applications.…”
Section: Materials Used To Fabricate Multi-materials Parts With Am Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the SLTAT method can be easily applied to existing multi-material 3D printers without adding additional heating equipment or post-processing steps ( Figure 8 b). For the purpose of improving adhesion of dissimilar thermoplastics without the need for chemical compatibilization, a bi-extruder head for FDM systems capable of printing two filaments through a single nozzle was developed [ 90 ]. This extruder’s unique feature is its convenient access to the internal channel, which allows the insertion of a static inter-mixer, thus enabling the deposition of mechanically interlocked extrusions consisting of two non-combustible polymers.…”
Section: Systematic Review Of Current Researchmentioning
confidence: 99%
“…Khondoker et al. [ 28,29 ] developed a custom‐made thermoplastic tri‐extruder compatible with FFF printers (see Figure a). The printing head has two angled input channels made of a metal alloy (brass – C36000) for feeding thermoplastic materials and a third one in the middle, made of a reusable stainless‐steel dispensing needle (22G) assigned to the extrusion of a central fluid core.…”
Section: General Background On Coaxial Am Technologiesmentioning
confidence: 99%